Analysis of Mangrove Canopy Cover with MonMang Application in Gemuruh River, West Sumatra, Indonesia - Irtanti, Amartia Eksa; Mukhtar, Erizal; Solfiyeni, Solfiyeni (Jurnal Biologi Tropis, 2025)
Mangrove canopies play a vital role in the photosynthetic process through their structure and density. The denser the canopy, the more difficult it is for sunlight to penetrate, making it less likely for mangroves in the seedling and sapling stages to receive adequate sunlight. This study aims to determine the mangrove canopy cover using the MonMang application and to determine the influence of environmental factors on mangrove trees. One method for measuring this is by applying the MonMang application in the mangrove forest of Sungai Gemuruh, Pesisir Selatan Regency, to determine canopy width within the ecosystem. The line transect method was used to estimate canopy cover, with transects laid from the shoreline inland through areas with true mangrove vegetation. Along the transects, 10 × 10 m plots were established. The MonMang application was applied to each plot to measure canopy cover, accompanied by data analysis, including the calculation of mangrove tree density. The results showed that the average canopy cover was higher along Transect II (76.88%) compared to Transect I (75.72%). Based on this study, it can be concluded that the estimated canopy cover in the Sungai Gemuruh Tourism Area falls into the category of very dense canopy cover.